The Effect of Work Stress And Work Environment osn Employee Performance at PT PLN (Persero) Up3 Palopo - Afsah; Muhammad Kasran; Sari Ratna Dewi (LP2M IAIN Palopo, 2025)
This study aims to examine the influence of work stress and work environment on employee performance at PT PLN (Persero) UP3 Palopo. In an increasingly competitive era of globalization, companies need to increase competitiveness that cannot be separated from employee contributions, the balance between personal life and work is the most important aspect in improving employee performance. This study uses a quantitative method that focuses on data collection and statistical analysis that aims to answer the researcher's questions and test the hypothesis. The population in this study were 30 employees of PT PLN (Persero) UP3 Palopo. The sample in this study was 30 employees of PT PLN (Persero) UP3 Palopo. Data collection was carried out using primary data. Data were obtained through distributing questionnaires to respondents, each item was scored on a Likert scale where each item was scored from (1) to (5).